2010
DOI: 10.4314/jasem.v11i4.55195
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ascomycetous Fungi from a Tertiary Institution Campus Soil

Abstract: This paper presents a survey of three iterative methods for the solution of linear equations has been evaluated in this work. The result shows that the Successive Over-Relaxation method is more efficient than the other two iterative methods, considering their performance, using parameters as time to converge, number of iterations required to converge, storage and level of accuracy. This research will enable analyst to appreciate the use of iterative techniques for understanding linear equations. @ JASEM The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Saccharomyces cerevisiae is widespread in nature -can be found on plants, fruits, in soils; it is a common colonizer of mucosal surfaces, a part of the normal flora of the gastrointestinal tract, respiratory tract, and vagina, but can cause a wide variety of clinical syndromes [24]. In the accessible literature, only a single study concerning soil yeasts from area of children's recreational areas can be found [8]. Soil samples taken from areas subject to intensive student and child use at the University of Ilorin (Nigeria), region of a high desert temperature, registered total fungal colony counts (not only yeasts) ranging between 5.8×10 2 and 1.63×10 2 per g of soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharomyces cerevisiae is widespread in nature -can be found on plants, fruits, in soils; it is a common colonizer of mucosal surfaces, a part of the normal flora of the gastrointestinal tract, respiratory tract, and vagina, but can cause a wide variety of clinical syndromes [24]. In the accessible literature, only a single study concerning soil yeasts from area of children's recreational areas can be found [8]. Soil samples taken from areas subject to intensive student and child use at the University of Ilorin (Nigeria), region of a high desert temperature, registered total fungal colony counts (not only yeasts) ranging between 5.8×10 2 and 1.63×10 2 per g of soil.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of children, common users of sandpits, school sports fields and park playgrounds, are particularly at risk of being infected. In the available literature, a paucity of information exists regarding soil yeasts from recreational areas intensely used by humans, especially children [7,8]. The aim of the present study was to evaluate the quantitative and qualitative profiles of yeast fungi in the soil of recreational areas for children in selected districts of Łódź, Poland.…”
Section: Isolation and Identification Of The Fungimentioning
confidence: 99%
“…The soil mycoflora were isolated from soil samples that were randomly collected using sterile soil auger at a depth of 0-15 cm from twenty-four (24) different locations, twelve (12) each from the lowland and upland areas (i.e, six from cultivated and uncultivated of each site respectively). The soil samples were placed into polythene bags, properly labelled and transported to Mycology laboratory, Biological Sciences Department, Usmanu Danfodiyo University, Sokoto within one hour of collection for fungal analysis following modified techniques of Gaddeyya et al [2] and Durowade et al [14] Table 1.…”
Section: Methods Of Soil Sample Collectionmentioning
confidence: 99%